MAY 1992 ACTIVITY REPORT--MN - LANE, WES (Tufts Archival Research Center, 2007)
Activity report regarding the Minnesota legislature and the passage of the new privacy bill. Discusses Wes Lane's involvement in addressing issues surrounding the bill at the various labor events. Highlights the use to newspaper publications to draw attention to the issue. Mentions that anti-smoking advocacy has been quiet as of late but that monitoring their involvement is necessary.